Crafting SME Business Model for International Expansion with Data-Driven Services - Eriksson Taina; Heikkilä Marikka; Nummela Niina (Routledge, 2022)
Contemporary world is increasingly data driven. Data that people produce, collect from others or buy from specialised suppliers concerning markets or customers. A growing number of companies – including small and medium-sized enterprises (SMEs) – are aware of the business opportunities that this development creates. The internationalisation process of a firm starts after an individual within the firm has recognised business opportunities in international markets. International opportunities – as well as any other entrepreneurial opportunities – emerge in an iterative process of shaping and development during which the initial ideas are elaborated, refined, changed, or rejected. The selection of cases is a crucial decision in the research process and should therefore be made after careful consideration and a critical evaluation of all alternatives. The interview data were enriched with internal firm documents related concerning the design of the business model for data-driven services, comprising business model canvas drafts and plans for change.
Business Models and Firm Internationalisation